Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)x=\(\frac{5}{12}\)
b)x=\(\frac{39}{35}\)
c)-x=-\(\frac{4}{21}\)
x=\(\frac{4}{21}\)
Tìm x biết:
5. ( x-1 ) - 7.( x-2 ) = 2x -39
Tìm x thuộc Z biết:
x - 3 - 14.( x-2 )= -3x -3
\(3x+7⋮x-2\)
5 ( x - 1 ) - 7 ( x - 2 ) = 2x - 39
<=> 5x - 5 - 7x + 14 = 2x - 39
<=> 5x - 7x - 2x = -39 + 5 - 14
<=> -4x = -48
<=> x = 12
x - 3 - 14.( x-2 )= -3x -3\(\Rightarrow\chi-3-28-14\chi-28=-3\chi-3\)
\(\Rightarrow\chi-3-28+3=-3\chi-3\)
\(\Rightarrow\chi-28=11\chi\)
\(\Rightarrow\chi-11\chi=28\)
\(\Rightarrow10\chi=28\Rightarrow\chi=2,8\left(kot.m\chi\inℤ\right)\)
tìm x biết
x-1/2=-2/3
\(x-\frac{1}{2}=-\frac{2}{3}\)
\(x=\frac{-2}{3}-\frac{1}{2}=\frac{-1}{6}\)
2/7-x=-3/4
\(\frac{2}{7}-x=-\frac{3}{4}\)
\(x=\frac{2}{7}-\left(-\frac{3}{4}\right)=\frac{29}{28}\)
\(\frac{6}{x^2+2}+\frac{12}{x^2+8}=3-\frac{7}{x^2+3}\)
\(\Leftrightarrow6\left(x^2+8\right)\left(x^3+3\right)+12\left(x^2+2\right)\left(x^2+3\right)=3\left(x^2+2\right)\left(x^2+8\right)\left(x^2+3\right)-7\left(x^2+8\right)\left(x^2+2\right)\)
\(\Leftrightarrow18x^4+126x^2+216=3x^6+32x^4+62x^2+32\)
\(\Leftrightarrow18x^2+126x^2+216-3x^6-32x^4-68x^2-32=0\)
\(\Leftrightarrow-14x^4+58x^2+184-3x^6=0\)
\(\Leftrightarrow x=\pm2\)
\(\Rightarrow x=\pm2\)